Crystal structures and mechanical properties of M (Mg, Sr, Ba, La)xCa1−xB6 solid solution: A first principles study. Issue 6 (1st May 2016) - Luo, Kan; Qiao, Yingjie; He, Shihong; Zha, Xian-Hu; Huang, Qing; He, Jian; Lin, Cheng-Te; Du, Shiyu
Abstract: First-principles calculations are performed in this work to study the effects of M (M=Mg, Sr, Ba, La) substitution in CaB6 . Both electronic structure and mechanical properties are examined. The current results indicate that the substitution of Ca by M atoms causes the lattice constants to scale linearly with the variation of x . The shear moduli of M x Ca1− x B6 are found to be related to the valence d-electron Mulliken charges in the lattice. The hardnesses of M (M=Mg, Ca, Sr, Ba, La)B6 and their solid solution are calculated by analyzing the overlap populations of the B–B bonds in the solid solution system.